Adult Hope Scale: validation in older adults - Kate Labrosciano; Jillian Dorrian; Braam Lowies; Roslyn Russell; Kurt Lushington (Australian Journal of Psychology, 2025)
Objective The Adult Hope Scale (AHS) is a widely used measure of hope and is reported to contain two distinct but interrelated constructs of agency (motivation to achieve goals) and pathways (planning routes to goals). Hope is thought to play a key role in the wellbeing of older people and while the AHS has been validated in young/middle-aged adults, the factor structure remains to be tested in older adults.Method Using computer-assisted personal communication, the AHS was completed by 1454 older Australians (726 F, age (mean (sd)) = 66.4 (5.81) y, range 55–84 y) stratified according to gender, location (metropolitan vs non-metropolitan), retirement status (yes/no) and age (55–65 vs 65 + y). Dimensionality was tested by (i) bifactor modelling (one-factor, two-factor and a bifactor model with a general factor, Hope, and two specific factors, Agency and Pathways) and (ii) exploratory graph analysis (which uses community detection algorithms to cluster variables into factors). Cross-gender invariance was also tested. Hope scores were compared between demographics and wellbeing (i.e. WHO-5 mental wellbeing and positive/negative coping questionnaire) groupings.Results Both bifactor modelling and exploratory graph analysis reveal that the AHS is unidimensional. Gender was shown to be invariant. Hope scores were comparable between demographic groupings, but higher scores were observed in older adults with higher mental wellbeing and positive coping with effect sizes in the small to medium range.Conclusions This study confirms that the AHS is a unidimensional scale and can be used to reliably measure hope in older Australian men and women.